2012
DOI: 10.1002/app.37595
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light aging properties of PVC/CaCO3 composites

Abstract: The ultraviolet radiation aging behaviors of PVC/CaCO 3 and PVC/CaCO 3 /macromolecular modifier composites were studied through whiteness measurement, Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, scanning electron microscopy, and mechanical properties test. It was found that nano-CaCO 3 particles used as ultraviolet light screening agents could significantly enhance the antiaging properties of PVC materials. Due to the macromolecular modifier coated on nano-CaCO 3 particles, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Cho and Choi 22 and Kim et al 23 mentioned that addition of TiO 2 particle absorb harmful wavelengths in solar radiation and protect the polymer matrix from the photochemical degradation. 18 The study confirmed that the modified nano CaCO 3 filler is capable of solving the issues related to UV radiation aging and its influence on the mechanical strength retention. 18 The study confirmed that the modified nano CaCO 3 filler is capable of solving the issues related to UV radiation aging and its influence on the mechanical strength retention.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Cho and Choi 22 and Kim et al 23 mentioned that addition of TiO 2 particle absorb harmful wavelengths in solar radiation and protect the polymer matrix from the photochemical degradation. 18 The study confirmed that the modified nano CaCO 3 filler is capable of solving the issues related to UV radiation aging and its influence on the mechanical strength retention. 18 The study confirmed that the modified nano CaCO 3 filler is capable of solving the issues related to UV radiation aging and its influence on the mechanical strength retention.…”
Section: Introductionsupporting
confidence: 56%
“…11,18 They form a barrier between polymer matrix and light source and thus preventing the photodegradation of polymer. It is well recognized that inorganic fillers, such as CaCO 3 , ZnO, and TiO 2 particles, can be used as ultraviolet light screening agents in polymer matrix.…”
Section: Uv Shielding Properties Of Pvc Composites and Mechanical Promentioning
confidence: 99%
See 3 more Smart Citations